Data logger for medical device coordination framework - Gundimeda, Karthik (Kansas State University, 2011)
A software application or a hardware device performs well under favorable conditions. Practically there can be many factors which effect the performance and functioning of the system. Scenarios where the system fails or performs better are needed to be determined. Logging is one of the best methodologies to determine such scenarios. Logging can be helpful in determining worst and effective performance. There is always an advantage of levels in logging which gives flexibility in logging different kinds of messages. Determining what messages to be logged is the key of logging. All the important events, state changes, messages are to be logged to know the higher level of progress of the system. Medical Device Coordination Framework (MDCF) deals with device connectivity with MDCF server. In this report, we propose a logging component to the existing MDCF. Logging component for MDCF is inspired from the flight data recorder, “black box”. Black box is a device used to log each and every message passing through the flight‟s system. In this way it is reliable and easy to investigate any failures in the system. We will also be able to simulate the replay of the scenarios. The important state changes in MDCF include device connection, scenario instantiation, initial state of MDCF server, destination creation. Logging in MDCF is implemented by wrapping Log4j logging framework. The interface provided by the logging component is used by MDCF in order to log. This implementation facilitates building more complex logging component for MDCF.
Keywords: Data logger; Device coordination framework; Computer Science (0984); Information Technology (0489)